Mass balance of nickel manganese cobalt cathode battery recycle process - Sri Handayani; Wahyudi Isqi Shahril; Ismojo Ismojo; Sri Rahayu; Yurian Ariandi Andrameda; Muhammad Dikdik Gumelar; Hanif Yuliani; Dita Adi Saputra; Saddam Husin (BIORE Scientia Publisher, 2024)
Batteries made from lithium, nickel, manganese, and cobalt are widely used, especially in the electrical industry, because they have high specific capacity, high safety, and low production costs. According to the International Energy Agency (IEA), the consumption of batteries used for electric vehicles will increase from 8 million in 2019 to 50 million in 2025 and to 140 million in 2030. As a result, the waste produced is also increasing. This type of lithium ion battery (LIB) which contains heavy metal elements such as nickel, manganese and cobalt can be recycled. This research aims to calculate the mass balance of the recycling process for nickel manganese cobalt (NMC) battery cathodes. The processing process begins with mixing, leaching, filtration, drying the results of the filtration process, molarity adjustment, Flame Assisted Spray Pyrolysis, and calcination. Based on the results of mass balance calculations for the NMC recycle battery cathode, the amount obtained was 43.427 kg/batch from 100 kg of cathode waste raw material. Apart from that, data was obtained on the metals that were successfully recycled, namely NiO, MnO, CoO, Fe2O3, MgO, Al2O3, Cr2O3, and Li2O. The research results provide information that NMC battery waste can be an opportunity for the NMC metal supply chain and can reduce environmental pollution.